KARAKTERISTIK MIKROKAPSUL Lactobacillus plantarum DAN STABILITASNYA DALAM PRODUK SELAI SALAK - Nurwulan Purnasari; Betty Sri Laksmi Jenie; Lilis Nuraida (Jurnal Teknologi dan Industri Pangan, 2015)
Microencapsulation a technique that can be used to improve the viability of probiotic during food processing and through the intestinal tract. Two probiotic candidates (Lb. plantarum BSL and Lb. plantarum 2C12) were encapsulated using 3% sodium alginate and soybean oil (0.2% Tween 80). The objectives of the study were to evaluate the effectivity of microencapsulation technique by emulsion method on the probiotic survival, heat resistance, injured cell, and tolerance to bile salt (0.5%) and low pH (pH 2). The encapsulated probiotics were then incorporated into snake fruit jam and evaluated for their viability during storage in room temperature for 4 weeks. The results showed that both microencapsulated probiotics demonstrated good survival with high viability (11 Log CFU g-1). Heat resistance of the encapsulated strains at 50ºC was better than their free cells, although higher temperatures (60-70ºC) would lowered the number of survivors. Heating at 50-70ºC caused injury to all probiotics cells either free or encapsulated. The survival of all encapsulated probiotics to bile salt and low pH were also better than their free cells. Encapsulated probiotic bacteria in snake fruit jam showed good viability throughout the four weeks of storage, whereas the free probiotic lost all their viability within two weeks. The total yeast and mold count of the probiotic snake fruit jam at 4 week-storage it was still approximately below the maximum standard. The results suggested that microencapsulation of probiotic by emulsion method is suitable to develop snake fruit jam as fruit based probiotic product.